BÉLA BARTÓK: “CONCERTO FOR ORCHESTRA”. ELEMENTS OF TURKISH FOLKLORE IN THE SOURCES OF A MASTERPIECE - SZAKÁCS, Boglárka (Studia Universitatis Babes-Bolyai Musica, 2019)
Béla Bartók’s Concerto for Orchestra represents one of the masterpieces of the 20th century. In the field of musicology there are countless analyses of this work from different points of view. The Concerto combines elements of Western classical music (for instance the use of the sonata-form) and Eastern European folk music. The influence of the Hungarian, Slovakian, Romanian and Serbian folk music is evident in this work of Bartók, but there is limited information available about the traces of the last collecting tour of the composer and ethnomusicologist in 1936 to Anatolia, Turkey. Beside enumerating different sources of inspiration for this composition, present article aims to identify the influence of the Turkish Folk Music Collection in Béla Bartók’s Concerto.